Do Canadian sport and exercise medicine physicans and emergency physicians give consistent sport-related concussion management advice?. Issue 5 (11th March 2013) - Carson, James; Purcell, Laura; Davidson, Bruce; Garel, Alisha; Bell, Margaret; Moineddin, Rahim
Abstract : Objective: To identify differences and gaps in the recommendations to patients for the management of sport-related concussion among sport and exercise medicine physicians and emergency physicians. Design: A self-administered multiple-choice survey, which had been validated for content validity. Setting: Canada. Subjects: Physicians who have passed the diploma examination of the Canadian Academy of Sport and Exercise Medicine (CASEM-MDs) and physicians on the Canadian Association of Emergency Physicians (CAEP-MDs) database. Intervention: The survey link was emailed to 470 CASEM-MDs and to 789 CAEP-MDs across Canada. Outcome Measures: Key survey questions identified sources of concussion management information, usefulness of concussion diagnosis strategies, and whether physicians use common terminology when explaining cognitive rest strategies to patients after a sport-related concussion. Results: Only 71% of CASEM-MDs usually use the SCAT2, whereas 86% of CAEP-MDs never use the SCAT2. 75% of CASEM-MDs usually advise time off of work or school after a sport-related concussion and 64% of CAEP-MDs do likewise. Only 75% of CASEM-MDs usually utilise balance testing. When queried how cognitive rest can best be achieved after a sport-related concussion, many choices were appealing with no consistent consensus. Conclusions: We identified a lack of consistency in the implementation of recommendations for sport-related concussion patients. It appears that the SCAT2 is utilised more in the office setting than in the emergency department. More recent strategies such as balance testing have not gained consistent usage, even among physicians with recognised expertise in concussion management. Better knowledge translation efforts should target both of these groups of physicians. Acknowledgements: Special thanks go to Paul Krueger, Leigh Hayden and the other 18 participants in the validation of our survey. Competing interests: None.